A collagen hydrolysate/milk protein-blend stimulates muscle anabolism equivalently to an isoenergetic milk protein-blend containing a greater quantity of essential amino acids in older men. Issue 6 (June 2021) - Brook, M.S.; Scaife, P.; Bass, J.J.; Cegielski, J.; Watanabe, S.; Wilkinson, D.J.; Smith, K.; Phillips, B.E.; Atherton, P.J.
Summary: Background & aims: Nutritional composition is key for skeletal muscle maintenance into older age. Yet the acute effects of collagen protein blended with other protein sources, in relation to skeletal muscle anabolism, are ill-defined. We investigated human muscle protein synthesis (MPS) responses to a 20 g blend of collagen protein hydrolysate + milk protein (CP+MP, 125 ml) oral nutritional supplement (ONS) vs. 20 g non-blended milk protein source (MP, 200 ml) ONS, in older adults. Methods: Healthy older men (N = 8, 71±1 y, BMI: 27±1 kg·m −2 ) underwent a randomized trial of 20 g protein, from either a CP+MP blend (Fresubin®3.2 kcal DRINK), or a kcal-matched (higher in essential amino acids (EAA) ONS of MP alone. Vastus lateralis (VL) MPS and plasma AA were determined using stable isotope-tracer mass spectrometry; anabolic signaling was quantified via immuno-blotting in VL biopsies taken at baseline and 2/4 h after ONS feeding. Plasma insulin was measured via enzyme-linked immunosorbent assay (ELISA). Measures were taken at rest, after the feed (FED) and after the feed + exercise (FED-EX) conditions (unilateral leg exercise, 6 × 8, 75% 1-RM). Results: MP resulted in a greater increase in plasma leucine (MP mean: 152 ± 6 μM, CP+MP mean: 113 ± 4 μM (Feed P < 0.001) and EAA (MP mean: 917 ± 25 μM, CP+MP mean: 786 ± 15 μM (Feed P < 0.01) than CP+MP. CP + MP increased plasma glycine (peak 385 ± 57 μM (P < 0.05)), proline (peak 323 ± 29 μM (P < 0.01)) and non-essential amino acids (NEAA) (peak 1621 ± 107 μM (P < 0.01)) with MP showing no increase. Plasma insulin increased in both trials (CP+MP: 58 ± 10 mU/mL (P < 0.01), MP: 42 ± 6 mU/mL (P < 0.01), with peak insulin greater with CP+MP vs. MP (P < 0.01). MPS demonstrated equivalent increases in response to CP+MP and MP under both FED (MP: 0.039 ± 0.005%/h to 0.081 ± 0.014%/h (P < 0.05), CP+MP: 0.042 ± 0.004%/h to 0.085 ± 0.007%/h (P < 0.05)) and FED-EX (MP: 0.039 ± 0.005%/h to 0.093 ± 0.013%/h (P < 0.01), CP+MP: 0.042 ± 0.004%/h to 0.105 ± 0.015%/h, (P < 0.01)) conditions. FED muscle p-mTOR fold-change from baseline increased to a greater extent with CP+MP vs. MP (P < 0.05), whilst FED-EX muscle p-eEF2 fold-change from baseline decreased to a greater extent with CP+MP vs. MP (P < 0.05); otherwise anabolic signaling responses were indistinguishable. Conclusion: Fresubin®3.2 kcal DRINK, which contains a 20 g mixed blend of CP+MP, resulted in equivalent MPS responses to MP alone. Fresubin® 3.2 Kcal DRINK may provide a suitable alternative to MP for use in older adults and a convenient way to supplement calories and protein to improve patient adherence and mitigate muscle mass loss.